UPAYA EDUKASI RISIKO OBESITAS “RETAS” PADA KELUARGA DI WILAYAH KOTA SURABAYA - Putri, Linta Meyla; Tjokro, Silvia Haniwijaya; Wijaya, Hermanto (Community Development in Health Journal, 2023)
Introduction & Aim: While the issue of malnutrition hasn't been completely overcome, the issue of overweight and obesity seems to be becoming worse. Obesity is a phenomenon similar to an iceberg that appears straightforward on the surface. If not treated right once, it would endanger the sustainability of future generations. Families and their members will have more access to complete health care. The aim of this activity is to carry out extensive community service projects that educate about the risks of obesity using a family-centered approach. Method of Activity: Educational Activities "RETAS" or Risk of Obesity is one of the health promotion activities with a family approach. The educational activity "RETAS" was carried out in Gubeng District, Surabaya, in December 2022. The implementation of community service activities included filling out pre-tests, giving materials, filling out food diaries, food diary, demonstration of physical activity, and post-tests. Activity. The "RETAS" activity was filled with the provision of comprehensive education, including obesity prevention, a community movement program for healthy living, balanced nutrition guidelines followed by filling out a food diary according to WHO guidelines, demonstration of physical activity, also distribution of media leaflets and booklets. Results: Participants' understanding increased by 72% after delivering education and materials. Discussion: Leaflets and booklets have been proven to increase participants' knowledge of the risk of obesity in families. Prevention of the risk of obesity with a comprehensive family approach through "RETAS" Education is hoped to be adopted as one of the health promotion efforts in urban and rural areas.